Características familiares de los hogares costarricenses - Reuben Soto, Sergio (2001)
This work gathers the results of a research funded by the Vicerectoría de Investigación of the University of Costa Rica, to determine the conformation of the homes computed by the Household Survey of July 1993 by the General Directorate of Statistics and Censuses of the Costa Rican government, according to family relationships among its members. A typology of households is elaborated, which was then used to collect census information from the Population Census of 2001. The results distribute the surveyed households in 8 types according to their family characteristics and collect demographic characteristics of their heads and their members.